Rituximab in refractory chronic inflammatory demyelinating polyneuropathy. Issue 5 (21st January 2020) - Muley, Suraj A.; Jacobsen, Bill; Parry, Gareth; Usman, Uzma; Ortega, Erik; Walk, David; Allen, Jeff; Pasnoor, Mamatha; Varon, Matthew; Dimachkie, Mazen M.
Abstract: Introduction: Chronic inflammatory demyelinating polyneuropathy (CIDP) is a disorder in which early effective treatment is important to minimize disability from axonal degeneration. It has been suggested that some patients with CIDP may benefit from rituximab therapy, but there is no definitive evidence for this. Methods: Baseline and post–rituximab‐therapy neuromuscular Medical Research Council (MRC) sum scores, Inflammatory Neuropathy Cause and Treatment (INCAT) disability score, and functional status were assessed in 11 patients with refactory CIDP. Results: The MRC sum score, INCAT disability score, and functional status improved in all patients after rituximab therapy. Discussion: Our study provides evidence of the efficacy of rituximab therapy in at least some patients with CIDP. A placebo‐controlled study to assess the effectiveness of rituximab therapy in CIDP with and without nodal antibodies is required to identify disease markers that predict responsiveness. Abstract : See editorial on pages 549–551 in this issue .